Effective assessment of low times MET amplification in pleural effusion after epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs) acquired resistance: Cases report. Issue 1 (January 2018) - Wang, Chang-guo; Zeng, Da-xiong; Huang, Jian-an; Jiang, Jun-hong
Abstract: Rationale: The mechanism of the first-generation epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs) acquired resistance included T790M mutation, cellular-mesenchymal to epithelial transition factor (MET) or EGFR amplification, PIK3CA mutation, and transformation to small cell lung cancer. MET amplification accounted for only about 5% of the resistance cases. Patients concerns: Few report detected MET amplification in pleural effusion. Here, we reported 2 lung adenocarcinoma cases with MET amplification in pleural effusion rapidly responded to crizotinib after EGFR-TKIs acquired resistance. Diagnoses: Biopsy via bronchoscopy, next-generation sequencing (NGS) in pleural effusion. Interventions: EGFR-TKIs (Icotinib), MET inhibitor crizotinib. Outcomes: After a progression-free survival of 9 months and 23months, respectively, both cases progressed accompanying with pleural effusion. Results of NGS in pleural effusion showed MET amplification (2–3 times) in both cases. The 2 patients were treated with a MET inhibitor crizotinib and rapidly responded. Conclusion: MET amplification in pleural effusion could predict a perfect response to crizotinib after EGFR-TKIs acquired resistance, even only a low times gene amplification.